1993
DOI: 10.1128/jvi.67.8.4932-4944.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neutralizing monoclonal antibodies to linear and conformation-dependent epitopes within the first and second variable domains of human immunodeficiency virus type 1 gp120

Abstract: A number of linear and conformation-dependent neutralizing monoclonal antibodies (MAbs) have been mapped to the first and second variable (Vi and V2) domains of human immunodeficiency virus type 1 (HIV-1) gp120. The majority of these MAbs are as effective at neutralizing HIV-i infectivity as MAbs to the V3 domain and the CD4 binding site. The linear MAbs bind to amino acid residues 162 to 171, and changes at residues 183/184 (PI/SG) and 191/192/193 (YSVGSS) within the V2 domain abrogate the binding of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 58 publications
3
87
0
Order By: Relevance
“…The MoAbs used in this study are listed below, with their epitopes shown in brackets after the clone nomenclature: 11/65a (C1-aa102-121); 11/41a (C5-aa471-491); 11/4c (V2-aa152-181) [4,5]; 11/68b (V1/V2 discontinuous) [4,5]; 10/36c (V3-aa311-321); 10/54ow (V3-aa311-321); 11/85b (V3-aa311-321); ICR41 (V3-discontinuous); ICR38.1a (C4-aa427-436) [6]; ICR39.13 g (CD4 binding site discontinuous) [7] and 8/19b (gp120 discontinuous) [8].…”
Section: Gp120 Antigens and Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The MoAbs used in this study are listed below, with their epitopes shown in brackets after the clone nomenclature: 11/65a (C1-aa102-121); 11/41a (C5-aa471-491); 11/4c (V2-aa152-181) [4,5]; 11/68b (V1/V2 discontinuous) [4,5]; 10/36c (V3-aa311-321); 10/54ow (V3-aa311-321); 11/85b (V3-aa311-321); ICR41 (V3-discontinuous); ICR38.1a (C4-aa427-436) [6]; ICR39.13 g (CD4 binding site discontinuous) [7] and 8/19b (gp120 discontinuous) [8].…”
Section: Gp120 Antigens and Monoclonal Antibodiesmentioning
confidence: 99%
“…Finally, sera were tested for reactivity with a truncated gp120 molecule containing the N-terminal and V1/V2 regions of the envelope protein [5]. It is interesting to note that the V1/V2 region has been reported to be a target for neutralizing antibodies and is immunogenic in infected individuals [4]. A very restricted number of sera from the protein-immunized animals contained V1/V2 reactivity, while none of the sera from the DNA immunized mice contained detectable antibody levels (data not shown).…”
Section: Comparison Of the Immune Response Following Dna And Protein mentioning
confidence: 99%
“…Antibodies directed against V2 and V3 in general have potent virus-neutralizing capacity (Fung et al 1992, McKeating et al 1993. It is of interest that the predicted conformational changes between NSI and SI variants may affect antibody recognition which may provide SI variants with an escape from neutralizing antibodies.…”
Section: Virus Phenotype Evolutionmentioning
confidence: 99%
“…In the present study, the frequency of plasma anti-V2 Abs was between 53% and 85% for the three V1V2 fusion proteins and was comparable to results in the RV144 study, which reported 84% frequency, possibly due to using the same V1V2 fusion proteins for screening (9). In previous studies of sera of individuals chronically infected with HIV-1, anti-V2 Abs were detected at a much lower frequency (from 12% to 48%), but either the V2 antigens tested were different or plasma Abs were analyzed by different methods (47).…”
Section: Discussionmentioning
confidence: 90%
“…The frequency of anti-V2 Abs in the plasma of individuals infected with HIV-1 varies among studies, depending on the methods used and the population studied. Screening of immune plasma using V2 consensus peptides with the HxB2 sequence detected 12% and 21% positive sera from HIV-1-infected individuals (4, 5). Using V1V2 proteins expressing both conformation-dependent V2i and linear V2p epitopes, the frequency of plasma anti-V2 Abs is higher, yielding 30% and 48% in two studies (6, 7).…”
mentioning
confidence: 99%